Exploring The Roles of ChatGPT in Enhancing Writing Accuracy Among Undergraduate EFL Learners at a Public University in Battambang - Sovann Ly; Seihak Ron; Voithna Nhean; Chenda Soeurn (Jurnal Adabiya, 2026)
ChatGPT is one of the large language models among artificial intelligence tools being integrated to support language and academic writing in higher education. This research was conducted with clear purposes: (1) to examine the roles of ChatGPT in enhancing the writing accuracy of undergraduate EFL learners; (2) to investigate the challenges and limitations students face when using ChatGPT for writing improvement; (3) to identify whether there are differences between male and female undergraduate students in their educational comprehension and perceptions toward using ChatGPT in English writing skills. The study was conducted quantitatively, with 226 undergraduate students participating via a Google Forms survey administered through purposive sampling. Roles, Challenges, and perceptions were measured with a 5-point Likert-scale instrument and presented in both inferential and descriptive statistics. Results revealed that EFL students heavily use ChatGPT for writing assistance, reporting for grammar error identification and correction (M = 3.78, SD = 0.96) and sentence clarity enhancement (M = 3.72, SD = 0.83). Regarding general perspectives, students valued ChatGPT for fast global information retrieval (M = 3.69, SD = 0.89), while confidence in relying on its output was lower (M = 3.35, SD = 0.89). Major challenges were found in proper citation and academic attribution (M = 3.74, SD = 0.81), and overly complex or technical outputs (M = 3.72, SD = 0.77). A statistically significant gender difference in confidence from inferential analysis with an independent samples t-test was indicated (t (224) = 2.88, p = .004), with male students rated on self-assessed confidence (M = 3.75) while female students rated (M = 3.51). However, there is no statistically significant difference across academic year cohorts (p > .05) analyzed with One-Way ANOVA. ChatGPT is valued as a writing tool for assistance with grammar correction and draft enhancement among undergraduate students, while challenges related to verifying information, practicing citations, and varying self-confidence between genders were found as constraints to ChatGPT adoption. Practitioners should consider digital literacy training to master the effectiveness of AI writing accuracy. ABSTRAK ChatGPT adalah salah satu model bahasa besar di antara alat kecerdasan buatan (artificial intelligence) yang diintegrasikan untuk mendukung pemelajaran bahasa dan penulisan akademik di perguruan tinggi. Penelitian ini dilakukan dengan tujuan yang jelas: (1) untuk menguji peran ChatGPT dalam meningkatkan akurasi penulisan pembelajar EFL (English as a Foreign Language) tingkat sarjana; (2) untuk menyelidiki tantangan dan keterbatasan yang dihadapi mahasiswa saat menggunakan ChatGPT untuk peningkatan kualitas penulisan; (3) untuk mengidentifikasi apakah terdapat perbedaan antara mahasiswa laki-laki dan perempuan dalam pemahaman edukatif serta persepsi mereka terhadap penggunaan ChatGPT dalam keterampilan menulis bahasa Inggris. Penelitian ini dilakukan secara kuantitatif, dengan 226 mahasiswa tingkat sarjana berpartisipasi melalui survei Google Forms yang disebarkan menggunakan teknik purposive sampling. Peran, tantangan, dan persepsi diukur menggunakan instrumen skala Likert 5 poin dan disajikan dalam statistik inferensial maupun deskriptif. Hasil penelitian mengungkapkan bahwa mahasiswa EFL sangat memanfaatkan ChatGPT untuk bantuan penulisan, terutama dalam mengidentifikasi dan mengoreksi kesalahan tata bahasa (M = 3.78, SD = 0.96) serta meningkatkan kejelasan kalimat (M = 3.72, SD = 0.83). Terkait pandangan umum, mahasiswa mengapresiasi ChatGPT untuk penarikan informasi global yang cepat (M = 3.69, SD = 0.89), sedangkan tingkat keyakinan untuk bergantung pada hasil (output) AI tercatat lebih rendah (M = 3.35, SD = 0.89). Tantangan utama ditemukan pada sitasi dan atribusi akademik yang tepat (M = 3.74, SD = 0.81), serta luaran yang terlalu kompleks atau teknis (M = 3.72, SD = 0.77). Analisis inferensial dengan independent samples t-test menunjukkan adanya perbedaan keyakinan yang signifikan secara statistik berdasarkan gender (t(224) = 2.88, p = .004), di mana mahasiswa laki-laki memberikan penilaian lebih tinggi pada keyakinan diri (M = 3.75) dibandingkan mahasiswa perempuan (M = 3.51). Namun, tidak terdapat perbedaan yang signifikan secara statistik di antara kohort angkatan akademik (p > .05) berdasarkan analisis One-Way ANOVA. ChatGPT dinilai sebagai alat bantu penulisan yang bermanfaat untuk koreksi tata bahasa dan penyempurnaan draf di kalangan mahasiswa, meskipun tantangan terkait verifikasi informasi, praktik sitasi, serta variasi rasa percaya diri antargender menjadi kendala dalam adopsi ChatGPT. Para praktisi sebaiknya mempertimbangkan pelatihan literasi digital untuk mengoptimalkan efektivitas akurasi penulisan berbasis AI.